Quality Control Analysis Using FMECA Method in Identifying Critical Point in the Can Manufacturing Industry - Irawan, Michael Aria; Pulansari, Farida (Heuristic, 2025)
The tighter the competition between companies in gaining market access, the more companies compete to implement market transformation strategies. A business generally has the same main goal, which is to achieve optimal profits based on business growth in the long run. But besides that, the company must be able to maintain the quality of the products it produces or improve the quality of the products it produces, both in the form of services and goods. In this research PT XYZ is a company engaged in packaging manufacturing, including food and paint. The main purpose of this study is to find the Risk Priority Number (RPN) and Criticality Point using the FMECA method. FMECA aims to analyze the potential risks that can arise in tools, processes and systems. The results of the analysis of the RPN results and criticality points that there are 5 priority failure modes, namely the accumulation of too many production goods, the assemble control tool does not work, the raw materials hit each other, the raw materials suffer physical damage, and the machine often jams due to a lot of dust. The conclusion of this study is that the company can make improvements to its production process in an effort to improve the quality of its canned products through the details of improvements that have been determined.